Study of bulk and sub-event wet deposition in Gebze, Turkey - (:unkn) unknown (My University, 2003)
This study presents the chemical composition of bulk deposition during the period of February 1996-May 1997 and the chemical composition of sub-event wet deposition on 13 August 1997 in Gebze. Samples were analyzed for SO42-, NO3-, Cl-, Ca2+, Mg2+, K+, Na+, and NH4+ in addition to pH. The source of some ionic components in the bulk deposition such as K+ and Ca2+ were found to be the terrestrial regions, as expected. The (non-sea Cl-)/Cl- ratio of 0.05 suggests that the very large portion of Cl- in the bulk deposition was of marine origin. The ratio of (non-sea SO42-)/SO42- varied between 0.86 and 0.99, indicating that the main source of sulfate was not the sea. It is found that the sulfate and calcium concentrations were highest in summer and lowest in fall. The analysis of bulk deposition also indicated that nearly 24% of the events were acidic (pH < 5.6). During sub-event wet deposition collected on the same site pH decreased continually, and during the passage of cold front concentrations of Cl-, SO42- and NO3- increased. © 2004 Kluwer Academic Publishers.
Keywords: Determination of chemical sources; Enrichment factor; Sub-event sampling; Wet and bulk deposition